RESILIENSI PADA MAHASISWA SELAMA PEMBELAJARAN DARING - Asina Christina Rosito (Visi Sosial Humaniora, 2021)
The purpose of this study was to obtain an overview of the resilience of students during online learning. Participants in this study were 730 active students from various campuses in Sumatra, Java, and Papua. The research data was collected by distributing the adapted version of The Connor-Davidson Resilience Scale (CD-RISC). The data analysis technique used were statistical descriptive analysis and categorization of resilience scores and scores of each dimension. The results showed that the mean score for resilience was 96.24 (SD = 14.75), for the dimensions of personal competence, high standard, and tenacity was 31.23 (SD = 5.22), for the dimensions of trust to one's instinct, tolerance of negative affect was 26.12. (SD = 4.56), for the positive acceptance of change and secure relationship dimensions was 18.11 (SD = 3.74), for the control dimension was 11.86 (SD = 2.15), and for the spiritual influence dimension was 8.92 (SD = 1.30). Based on the categorization, it was found that there were 474 participants (64.9%) with high resilience, 247 people (33.8%) with moderate resilience, and 9 people (1.2%) with low resilience. Further discussion of the results is presented.